Law for Entrepreneurs - Mayer, Don; Warner, Daniel; Siedel, George J.; Lieberman, Jethro K. (Open textbook library., 2012)
Law for Entrepreneurs is an up-to-date textbook that covers the broad spectrum of legal issues that entrepreneurs must understand when starting and running a business. The text is organized to permit instructors to tailor the materials to their particular approach. The authors take special care to engage students by relating law to everyday events with their clear, concise and readable style. After introductory chapters covering the legal environment of business, Law for Entrepreneurs provides students with context and essential legal concepts relating to contracts, product liability, intellectual property, insurance, agency law, partnerships, corporations, and employment law. The text provides the vocabulary and legal savvy that entrepreneurs need to talk in an educated way to customers, suppliers, employees, creditors, shareholders, government regulators and other stakeholders — and to their own lawyers.